KOORDINASI LINTAS SEKTORAL DALAM PENGEMBANGAN PARIWISATA DI KABUPATEN LANDAK - Fuaddianto Fajar Satrio E.42009049 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2013)
The research is intended to determine how the Intersectoral Coordination in the Development of Tourism in Landak Regency with a focus on the effectiveness of coordination in tourism’s development . The title of this script is taken based on the problem of cross-sectoral coordination in tourism’s development that still can not be optimal compare with Intersectoral Coordination in tourism’s development in the other districts. This research use qualitative analysis in three stages: first analysis of the data reduction, data presentation and a final conclusion. The research location is in District Ngabang, Landak Regency. Subject of this research is the Department of Youths, Sports, Cultures and Tourisms with the Department of Public Working and Housing who are involve in the coordination of tourism’s development. The conclusion of this research is ; The coordination still can not be optimal cause by several factors: the lack of decisive leadership, the lack of dynamism in the coordination, formulation of authority and responsibility are not clear and the complexity of organization. The recommendation for coordination has been done is make changes to the horizontal coordination process by looking at the results that have been obtained for reconsideration in accordance with the coordination of the factors that must be corrected in accordance with its objectives. Keywords: Coordination, Cross-Sectoral, Tourism Development